English Teachers’ Preparedness in Technology Enhanced Language Learning During Covid-19 Pandemic – Students’ Voice - Situmorang, Komilie; Nugroho, Dwi Yulianto; Pramusita, Santa Maya (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2020)
Students’ voices matter because they tell us different perspectives of what happens in the classroom. This study focused on the students’ voices of the English Teachers’ technical and digital preparedness in technology-enhanced language learning. The study was designed in a descriptive quantitative method using a 4-point Likert scale questionnaire. This study recruited 105 nursing students to voice their teachers’ preparedness in the technology technology-enhanced learning during the pandemic. The result indicated the respondents’ voice expressed that their English teachers positively transformed along with the time. Teachers were found to be positively prepared in digital literacy, digital classroom, and digital assessment after a short period. Implications suggest that teachers and students adopt remote learning as it will soon be the new normal in Language Teaching.